Hannah Arendt: moral conscience and banality of human condition (2009)
If we define moral consciousness as the capacity to self-criticize and debate within the framework of reciprocal demands, then totalitarianism appears as one of its major challengers, since it has become a form of banalization and annihilation of life. Th